Sports and infections - Herrero, H. (Injury and Health Risk Management in Sports, 2019)
Acute infectious diseases are frequent among athletes and can result in training and competition absence. Since athletes are expected to return to training as soon as possible, the knowledge of these diseases, their clinical presentation, possible complications, transmission mechanisms, and prevention should be among the main concerns of sports medicine. Infectious diseases can be prolonged or aggravated by continuing physical activity and athletes also risk having other acute or chronic organ manifestations such as bronchitis or pneumonia, myocarditis, pericarditis, and other secondary complications, for this reason exercise should not be allowed during convalescence and recovery. In the case of elite athletes, the return-to-play decision is particularly important and consensus between scientific evidence and clinical experience is necessary. Although infectious diseases are highly prevalent in athletes, there is a scarcity of literature focused on evidence and guidelines for sports physicians regarding RTP decision. Each case should be individualized according to subjective and objective symptoms together with the patient`s progress in every particular case.